BLENDED LEARNING BERBASIS QUIPPER SCHOOL DALAM PEMBELAJARAN BAHASA INDONESIA DI SMAN 1 BANTAENG - Asdar Asdar; Jihad Talib (Universitas Muhammadiyah Tapanuli Selatan, 2021)
This study aims to describe the application of Quipper School-based blended learning to the process and learning outcomes of class XI IPA1 students in Indonesian language learning at SMA Negeri 1 Bantaeng. This research is a classroom action research. Data collection techniques, namely observation, documentation, and tests. The research method is qualitative descriptive analysis. The results of the action and process carried out showed that the attention of students in the first cycle was 63.43% and increased in the second cycle by 93.90%. Furthermore, student learning outcomes in the first cycle an average of 71 with a percentage of 67.74% completeness and an increase in the second cycle to 95 with completeness reaching 100%. The application of Quipper School-based blended learning can improve the process, independence, effectiveness, creativity and student learning outcomes in learning Indonesian in class XI IPA1 SMA Negeri 1 Bantaeng.